Differential subcellular distribution of neurolysin (EC 3.4.24.16) and thimet oligopeptidase (EC 3.3.24.15) in the rat brain - Massarelli, E. E.; Casatti, Cláudio Aparecido [UNESP]; Kato, A.; Camargo, ACM; Bauer, J. A.; Glucksman, M. J.; Roberts, J. L.; Hirose, S.; Ferro, E. S. (Elsevier B.V., 1999)
Immunohistochemistry was used to analyze the rat brain distribution of thimet oligopeptidase and neurolysin. Both enzymes appear ubiquitously distributed within the entire rat brain. However, neuronal perikarya and processes stained for neurolysin, while intense nuclear labeling was only observed for thimet oligopeptidase. These data suggest that neurolysin and thimet oligopeptidase, endopeptidases sharing several functional and structural similarities, are present in distinctive intracellular compartments in neuronal cells. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: nuclear enzyme; peptide; intracellular metabolism; neuropeptide; endopeptidase; oligopeptidase